1972
DOI: 10.1002/bjs.1800590417
|View full text |Cite
|
Sign up to set email alerts
|

A case of carcinoma of the colon in association with neurofibromatosis

Abstract: A case is presented of neurofibromatosis of the large bowel associated with a primary adenocarcinoma of the colon. This is believed to be the first report of such an association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Adenocarcinomas of the esophagus (63), stomach (64), colon (65,66), small intestine (67)(68)(69)(70)(71)(72), pancreas (72,73), gallbladder (74), and bile ducts (74,75) have been reported in patients with NF1. Taking into consideration the prevalence of these cancers in the general population, the association of adenocarcinomas in the colon, esophagus, stomach, biliary tract, and pancreas with NF1 may be incidental.…”
Section: Adenocarcinomamentioning
confidence: 98%
“…Adenocarcinomas of the esophagus (63), stomach (64), colon (65,66), small intestine (67)(68)(69)(70)(71)(72), pancreas (72,73), gallbladder (74), and bile ducts (74,75) have been reported in patients with NF1. Taking into consideration the prevalence of these cancers in the general population, the association of adenocarcinomas in the colon, esophagus, stomach, biliary tract, and pancreas with NF1 may be incidental.…”
Section: Adenocarcinomamentioning
confidence: 98%
“…Neurofibromatosis may also be associated with other malignant tumours such as carcinoid of the ampulla of Vater (Barber, 1976), adenocarcinoma of the pancreas (Kellar and Logan, 1977), adenocarcinoma of the colon (Jenkins and Gill, 1972), Wilms' tumour (Stay and Vauter, 1977), rhabdomyosarcoma (McKeen and Bodurtha, 1978) and leukaemia (Bader and Miller, 1978). The authors wish to report the association of primary adenocarcinoma of the duodenum in a young man suffering from cutaneous neurofibromatosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is the fourth report in the medical literature describing adenocarcinoma of the colon in the presence of neurofibromatosis. [2][3][4] There also have been seven case reports in the literature that indicate an association between neurofibromatosis and small-bowel adenocarcinoma. 5 It has been suggested that there is an association with adenocarcinoma of the stomach, 6 oesophagus, 7 and pancreas.…”
Section: Discussionmentioning
confidence: 94%
“…There are, however, only three case reports that indicate an association with adenocarcinoma of the colon. [2][3][4] This case report provides further evidence of a link between neurofibromatosis and adenocarcinoma of the colon.…”
mentioning
confidence: 86%